2013
DOI: 10.1111/bjd.12261
|View full text |Cite
|
Sign up to set email alerts
|

Topical therapies for the treatment of localized plaque psoriasis in primary care: a cost-effectiveness analysis

Abstract: SummaryBackground Topical therapies are a mainstay of psoriasis treatment, but they vary substantially in terms of cost. Objectives To determine the cost-effectiveness and optimal treatment sequence for psoriasis of the trunk, limbs and scalp. Methods Probabilities of response from a network meta-analysis were used to determine the short-term efficacy of topical therapies. Longer-term outcomes, including relapse, were informed by published evidence and clinical opinion. Benefits of treatment were measured as q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…). Twenty‐eight articles were published after the reviews that were conducted to inform the U.K.'s National Institute of Health and Care Excellence (NICE) guidelines for high‐quality psoriasis care . There was diversity in setting, perspective and national characteristics (Table ), psoriasis severity, design and evaluation type (Table S1; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Twenty‐eight articles were published after the reviews that were conducted to inform the U.K.'s National Institute of Health and Care Excellence (NICE) guidelines for high‐quality psoriasis care . There was diversity in setting, perspective and national characteristics (Table ), psoriasis severity, design and evaluation type (Table S1; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…There was diversity in setting, perspective and national characteristics (Table ), psoriasis severity, design and evaluation type (Table S1; see Supporting Information). Fifteen papers reported more than one type of comparison. In total, 71 comparisons between different interventions were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies mapped the Dermatology Life Quality Index (DLQI) to European Quality of Life-5 Dimensions (EQ-5D) utilities [35,57,59]; however, Woolacott et al [67] mapped the change in DLQI associated with different PASI response categories and baseline DLQI scores to changes in EQ-5D utility. The remaining studies either estimated utility values directly from study patients [22,26,58], stated utility values from previous studies were used without providing further details [43,56], or obtained utilities by response status defined by neither PASI nor DLQI from previous studies [60].…”
Section: Synthesis Of Cost-effectiveness Analysis Studiesmentioning
confidence: 99%
“…The main assumptions include patient compliance or adherence to treatments [49,60], length of treatment [31], productivity costs [58,62], hospitalization for non-responders [24,62,67], defining responders by PASI 90 (a 90 % reduction in the PASI score) [32] or PASI 50 (a 50 % reduction) [62] instead of PASI 75 (a 75 % reduction), a treatment-free response period [21], responding patients withdrawing from treatment [35,40], reduced response upon re-treatment [59], and disutility on intermittent therapy [62]. Furthermore, more than one time horizon was applied in some studies [23,32,35,40,46,48,60,71]. We found that in 20 studies, the sensitivity analyses had no impact on the final conclusions, whereas in 14 other studies, the cost-effectiveness conclusions were affected.…”
Section: Within the Studymentioning
confidence: 99%